Effects of cognition on the psychophysical function - Centa, D M; Jones, Q R (Perceptual and motor skills, 1985)
Previous investigation of the deterministic-sensory and the probability-sensory-learning models of psychophysical relationships have featured the manipulation of a single cognitive cue. The present study sought to expand these findings through the manipulation of multiple cognitive cues. Subjects made magnitude estimations of skin-area contact for each of two sets which varied identically in surface area but differed in that one set also varied in accelerative force. Within sets, three treatments featured systematic variation in the presentation of cognitive cues. Power functions were obtained for all treatments and the results supported the deterministic-sensory model. It was suggested, however, that resolution of the perception versus cognition issue must await the identification of innate and conditioned correlates of the subjective response to specific sensory stimuli.